Effects of carbonated beverage and fruit juice on salivary pH among children in orphanage of Bareilly city: an in vivo study - Agrawal, Anagha; Saxena, Shobhit; Baviskar, Bhairavi; Govilkar, Eshita S.; Mishra, Shweta D.; Nepale, Mayuri (International Journal of Basic & Clinical Pharmacology, 2023)
Background: High degree of urbanization and economic development have resulted in rapid changes in diet and lifestyles, because of which there is a tremendous increase in prevalence of dental caries in developing countries. The aim of the study is to assess the acidogenic potential of commonly consumed carbonated beverage and commercially available fruit juice at various time intervals among orphan children. Methods: This is an in vivo study in which 60 orphan children were included. Two beverage groups (carbonated beverage and fruit juice) were tested for salivary pH before having respective drinks (baseline) and after having drinks at specific time intervals (immediately after, after 15 min and 30 min). Intra-group and inter-group comparisons were done using Friedman test and Mann Whitney U test. Results: Both the groups showed decrease in salivary pH after consumption and recovery of salivary pH to baseline value after 30 min. Conclusions: Beverages produce a remarkable drop in the salivary pH as they contain organic acids and sugars but saliva by virtue of its buffering capacity nullifies this effect and after some time it comes to normal.